Analysis of Labour Market Inequality and Income Welfare: An Economic Comparative Study Graph between North Sumatra and West Sumatra Provinces - Noer, Muhammad Raihan; Febrianti, Gita; Sinaga, Era Widia Br; Nafisha, Nadya; Hutabalian, Relli Anisma; Nasution, Putri Andini; Nasution, Armin Rahmansyah (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
The analysis of inequality in labour and income welfare aims to determine how much inequality occurs in the labour market and income between North Sumatra Province and West Sumatra Province. The method in data collection uses secondary method by obtaining data through the Central Bureau of Statistics (BPS). Data analysis is explained through descriptions measured through 1) Expert labour index. 2) Skilled labour index. 3) Human development index. 4) Productive age worker index. 5) Net income index. This research results in inequality that. 1) West Sumatra Province has higher inequality than North Sumatra Province in Expert Labour. 2) West Sumatra Province has more skilled labour than North Sumatra Province. 3) West Sumatera Province dominates the Human Development Index more than North Sumatera Province. 4) The Productive Age Worker Index is more in North Sumatra Province than West Sumatra Province with the inequality value dominating superior.5) The Net Income Index in North Sumatra Province is superior to West Sumatra Province. Researchers suggest the government to be more responsive related to inequality and community welfare, especially in direct policies.